Sosialisasi Kurikulum Merdeka Belajar Sma Al-Idrisiyah Sekolah SMA Al Idrisiyah Tanjung Selor Fatimah Al -Zahrah Desa Gunung Sari Km 12 Kecamatan Tanjung Selor Kabupaten Bulungan - Iskandar; Budi Mulyadi; Irsyad Sudirman; Syaini; Jimmy Nasroan; Masruri; Wempi Feber; Yani Faturrachman; M. Ibnu Ashari. R (Setawar Abdimas, 2023)
Merdeka Curriculum is a curriculum with diverse intracurricular learning where content will be more optimal so that students have enough time to explore concepts and strengthen competencies. The independent teaching platform is an educational platform that can be used by educators as a medium for learning. The independent teaching platform is a driving force for educators in realizing pancasila learners who have various learning features. Based on various obstacles at Al Idrisiyah High School, including literacy, references, digital access, teacher competence, and time management, it is known that some teachers still rely on package books, both student books and teacher books as the only learning resource. While other learning resources are considered unimportant, it motivates us to carry out service activities with the theme of socialization of the independent curriculum which is in line with the independent curriculum launched by the Minister of Education and Culture in February 2022 as one of the Merdeka Belajar programs. The purpose of the socialization of the independent learning curriculum at Idrisiyah Senior High School in Gunung Sari Village, Tanjung Selor District, Bulungan Regency is to improve the quality of learning. The Merdeka curriculum focuses on essential materials and on developing the character of the pancasila student profile and is a step to transform education for the realization of Indonesia's Superior Human Resources which have pancasila student features. The implementation of the independent curriculum is a new thing, therefore Al-Idrisiyah High School continues to strive to equip teachers' knowledge so that teaching and learning activities that use the independent curriculum can later run optimally. In this Independent Learning Curriculum, there is no specialization program, so students can be free to choose subjects that suit their interests and talents. With this program, it can improve the quality of human resources. Because quality human resources can improve the progress of the nation. Kata kunci— curriculum, independent learning, Al-Idrisiyah High School;